2014
DOI: 10.1144/sp402.7
|View full text |Cite
|
Sign up to set email alerts
|

Sedimentary-rock-hosted epithermal systems of the Tertiary Eastern Rhodopes, Bulgaria: new constraints from the Stremtsi gold prospect

Abstract: Precious metal epithermal, sedimentary-rock-hosted prospects constitute a new class of ore deposits recently described in the Tertiary Eastern Rhodopes of southeastern Bulgaria. The Stremtsi prospect investigated in this contribution is located in a distal location with respect to the main cluster of sedimentary-rock-hosted Ada Tepe and Rosino gold prospects of the Eastern Rhodopes. The Stremtsi prospect is hosted by a Priabonian clastic sedimentary rock sequence, overlying metamorphic rocks of the Central Rho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“…In this hypothesis, melt production started as soon as the subducting slab reached the partial melting zone and continued throughout Late Cretaceous time fuelled by a continuous subduction until continental collision in latest Cretaceous time (Gallhofer et al 2015). On the other hand, recent research along the Alpine–Himalayan belt has revealed that many magmatic deposits previously assumed to be subduction related are in fact syn- or post-collisional (Shafiei, Haschke & Shahabpour, 2009; Moritz et al 2010; Imer, Richards & Creaser, 2013) and sometimes occur long (30–40 Ma) after the end of oceanic lithosphere subduction (Hou et al 2009, 2011).…”
Section: Proposed Geodynamic Modelmentioning
confidence: 99%
“…In this hypothesis, melt production started as soon as the subducting slab reached the partial melting zone and continued throughout Late Cretaceous time fuelled by a continuous subduction until continental collision in latest Cretaceous time (Gallhofer et al 2015). On the other hand, recent research along the Alpine–Himalayan belt has revealed that many magmatic deposits previously assumed to be subduction related are in fact syn- or post-collisional (Shafiei, Haschke & Shahabpour, 2009; Moritz et al 2010; Imer, Richards & Creaser, 2013) and sometimes occur long (30–40 Ma) after the end of oceanic lithosphere subduction (Hou et al 2009, 2011).…”
Section: Proposed Geodynamic Modelmentioning
confidence: 99%
“…This complex converging system resulted in Jurassic-Cretaceous and Paleogene subduction-related magmatism and ore formation, followed by various collision to post-orogenic magmatic and ore forming events throughout the Cenozoic (e.g. Marchev et al, 2005;Von Quadt et al, 2005;Perelló et al, 2008;Yigit, 2009;Moritz et al, 2014;Hou et al, 2015;Richards, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…12). A similar process of sulfate reduction was proposed for sedimenthosted epithermal deposits from Eastern Rhodopes (Moritz et al, 2014). However this mechanism is rarely proposed as an explanation for the origin of sulfur in classical shallow marine-continental volcanichosted epithermal deposits, as total or partial sulfur source.…”
Section: The Role Of Sulfate Reduction In the Mazarrón Depositmentioning
confidence: 73%